2006
DOI: 10.1124/dmd.105.008219
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Resistance Protein (Bcrp/Abcg2) Transports Fluoroquinolone Antibiotics and Affects Their Oral Availability, Pharmacokinetics, and Milk Secretion

Abstract: ABSTRACT:The breast cancer resistance protein (BCRP/ABCG2) is an ATPbinding cassette drug efflux transporter that extrudes xenotoxins from cells in intestine, liver, mammary gland, and other organs, affecting the pharmacological and toxicological behavior of many compounds, including their secretion into the milk. The purpose of this study was to determine whether three widely used fluoroquinolone antibiotics (ciprofloxacin, ofloxacin, and norfloxacin) are substrates of Bcrp1/BCRP and to investigate the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(120 citation statements)
references
References 34 publications
8
111
1
Order By: Relevance
“…ABCG2 expression is highly induced in the apical membrane of alveolar epithelial cells during late pregnancy and especially during lactation [30], and is involved in the secretion of drugs into milk. The milk-toplasma concentration ratio of topotecan [30], PhIP [30], acyclovir [30], nitrofurantoin [51], and ciprofloxacin [52] was markedly reduced in Abcg2 knockout mice, but not that of DHEAS and folate [30].…”
Section: Abcg2 (Bcrp/abcp/mxr)mentioning
confidence: 99%
See 2 more Smart Citations
“…ABCG2 expression is highly induced in the apical membrane of alveolar epithelial cells during late pregnancy and especially during lactation [30], and is involved in the secretion of drugs into milk. The milk-toplasma concentration ratio of topotecan [30], PhIP [30], acyclovir [30], nitrofurantoin [51], and ciprofloxacin [52] was markedly reduced in Abcg2 knockout mice, but not that of DHEAS and folate [30].…”
Section: Abcg2 (Bcrp/abcp/mxr)mentioning
confidence: 99%
“…For drugs, it has also been shown that BCRP limits the oral absorption of topotecan [29], salfasalzine [86], and ciprofloxacin [52]. Abcg2 has been shown to account for the efflux of intracellularly formed glucuronide and sulfate conjugates (E3040 glucuronide, E3040 sulfate, and 4-methylumbelliferone sulfate) [1]; the active form of the ester-type prodrug of ME3277 [38] in the small intestine; the biliary excretion of drugs such as nitrofurantoin [51], methotrexate [10], pitavastatin [25], and salfasalazine [86]; and the urinary excretion of methotrexate [10] and E3040 sulfate [56].…”
Section: Abcg2 (Bcrp/abcp/mxr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Chenodeoxycholate-3-sulfate [15] 131 Glycodeoxycholate [15] 2.0 Glycoursodeoxycholate [15] 4.1 Cholate [15,54] [15,54] 7.3/13 Deoxycholate [15,54] 5.2-13 Glycochenodeoxycholate [54] 2.0/2.9 Glychodeoxycholate [54] 2.4/5.4 Glycholate [54] 11/21 Taurochenodeoxycholate [15,54] 1.0-6.1 Taurocholate [15,54] 7.3-25 Taurodeoxycholate [15] 4.5-17 Taurourosdeoxycholate [15] 28 Ursodeoxycholate [15,54] 36 [60] Estrone [56] Bisantrene [67] Betamethasone [57] Riboflavin [68] Taurolithocholate sulfate [56] 37 a Cerivastatin [61] Cerivastain [61] 18 Uric acid [69] Vitamin K3 [ [70] Ciprofloxacin [71] Daunorubicin [56] 59 a Daunorubicin [67] Dexamethasone [57] Diclofenac [72] Diclofenac [72] 71-78 Dipyridamole [73] Digoxin [57] Doxorubicin [67,74] Dipyridamole [73] 6.4 a Enrofloxacin [75] Doxorubicin [56,76] Epirubicin [67] Fluvastatin [61] 5.4 Fluvastatin [61,62] Glibenclamide [77] 150 a Glibenclamide …”
Section: Substrates and Inhibitorsmentioning
confidence: 99%
“…ABCG2 mRNA expression was higher compared to other efflux transporter in the human small intestine, which is a rate-limiting barrier to oral drug absorption [64] . The important impact of ABCG2 on the intestinal absorption was further supported by several knockout mice research, which have indicated that ABCG2 affects the pharmacological and toxicological behavior of many drugs [65][66][67] . Also, polymorphisms might influence the role of ABCG2 in intestinal absorption.…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 90%